Three Types of Perceived Uncertainty About the Environment: State, Effect, and Response Uncertainty - Milliken, Frances J. (Academy of Management Review, 1987)
The research literature on environmental uncertainty is briefly reviewed to illustrate problems and inconsistencies in conceptualizing and measuring the construct. Three types of perceived uncertainty about the environment are described and their implications for the behavior of an organization's administrators are discussed. The failure to differentiate between these types may explain some of the confusion about environmental uncertainty.